PAJANAN OKUPASI DARI PASIEN TERINFEKSI HIV DI RSUP SANGLAH DENPASAR - Somia, Agus; Utama IM, Susila; Parwati Merati, Tuti (journal of internal medicine, 2010)
Health care personnel who have occupational exposure to blood and some body ! uids or tissues are at risk for HIVinfection. Aim of this study to know about characteristics of occupational exposure to HIV who cares in VCT-CST OutpatientClinic Sanglah Hospital Denpasar. A retrospective descriptive study was done among exposed persons who care in VCT-CSTOutpatient Clinic Sanglah Hospital Denpasar during 1 January 2006 ? 31 December 2007.Total 11 cases occupational exposure occurred in health care places, 9 cases occurrence in Sanglah Hospital and 2 casesoutside Sanglah Hospital. The profession of exposed persons were doctor (45%), medical student (18.2%) and nurse (18.2%).The type of exposure were percutaneous injury (72.7%). Severity of exposures included, 36.4% KP1 (small volume in shorttime), 45.5 % KP2 (large volume and/or long time or percutaneous injury with solid needle, or superfesial laceration), and18.18% KP3 (percutaneous injury with hollow needle, deep injury, visible blood on the device which caused the injury, injurywith needle which had been placed in a source patients artery or vein). HIV-positive class I patients (asymptomatic HIV or alow viral load) was 27.3 % and HIV-positive class II (symptomatic HIV or AIDS, acute seroconversion, or high viral load) was27.3%. about 72% exposed person taken postexposure prophylaxis with combination zidovudine and lamivudine for 4 weeks.Anti HIV status exposed persons at " rst time exposure, 3 month after exposure and 6 month after exposure were negative.We conclude that the most type of exposure were percutaneous with source of exposure each included HIV positive classI dan HIV positive class II. About two third of exposed person taken postexposure prophylaxis with zidovudine and lamivudinecombination. Anti HIV status exposed person a " rst time exposure, 3 month after exposure and 6 month after exposure werenegative.